Neural substrate of concurrent sound perception: direct electrophysiological recordings from human auditory cortex - Bidet-Caulet, Aurélie; Fischer, Catherine; Bauchet, Francoise; Aguera, Pierre-Emmanuel; Bertrand, Olivier (Frontiers in Human Neuroscience, 2008)
In everyday life, consciously or not, we are constantly disentangling the multiple auditory sources contributing to our acoustical environment. To better understand the neural mechanisms involved in concurrent sound processing, we manipulated sound onset asynchrony to induce the segregation or grouping of two concurrent sounds. Each sound consisted of amplitude modulated tones at different carrier and modulation frequencies, allowing a cortical tagging of each sound. Electrophysiological recordings were carried out in epileptic patients with pharmacologically resistant partial epilepsy, implanted with depth electrodes in the temporal cortex. Patients were presented with the stimuli while they performed an auditory distracting task. We found that transient and steady-state evoked responses, and induced gamma oscillatory activities were enhanced in the case of onset synchrony. These effects were mainly located in the Heschl's gyrus for steady-state responses whereas they were found in the lateral superior temporal gyrus for evoked transient responses and induced gamma oscillations. They can be related to distinct neural mechanisms such as frequency selectivity and habituation. These results in the auditory cortex provide an anatomically refined description of the neurophysiological components which might be involved in the perception of concurrent sounds.